Governing markets as knowledge commons - Dekker, Erwin 1984-; Kuchař, Pavel (Cambridge studies on governing knowledge commons, 2022)
Knowledge commons facilitate voluntary private interactions in markets and societies. These shared pools of knowledge consist of intellectual and legal infrastructures that both enable and constrain private initiatives. This volume brings together theoretical and empirical approaches that develop and apply the Governing Knowledge Commons framework to the evolution of various kinds of shared knowledge structures that underpin exchanges of goods, services, and ideas. Chapters offer vivid and illuminating case studies that illustrate this conceptual framework. How did pooling scientific knowledge enable the Industrial Revolution? How do social networks underpin the credit system enabling the Agra footwear market? How did the market category Scotch whisky emerge and who has access to it? What is the potential of blockchain-ledgers as shared knowledge repositories? This volume demonstrates the importance of shared knowledge in modern society